Operation and maintenance for floating wind turbines: A review. (July 2022) - McMorland, J.; Collu, M.; McMillan, D.; Carroll, J.
Abstract: This paper reviews the existing literature surrounding floating offshore wind (FOW) operations and maintenance (O&M) models. A review of the technology is presented with a comparison with current practise for bottom-fixed offshore wind O&M activities. This article divides existing publications into the following categories: cost modelling, O&M modelling, and safety/limiting factors. A review of the case studies used within these publications shows trends towards development in Northern Europe. Factors considered during cost modelling are discussed with a review of levelised cost of energy results for the three main types of floating support structure. The key O&M inputs for FOW applications are identified and then analysed detailing the key differences between floating and bottom-fixed applications. Finally, the publications detail the impact of the motion of the turbine on O&M activities are discussed. Key areas of FOW O&M research are identified with details of current research gaps and recommendations for future work. Highlights: Review of operation and maintenance (O&M) models specifically for floating wind. Review of case studies in the literature and their key input factors. Discussion of differences of O&M inputs between floating and fixed turbines. Recommended changes needed for fixed O&M models for floating simulations. Gaps in the literature identified with recommendations for future research.